2021
DOI: 10.1039/d1ra00965f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of enzymatically cross-linked gelatin/cellulose nanocrystal composite hydrogels

Abstract: Gelatin is an attractive hydrogel material because of its excellent biocompatibility and non-cytotoxicity, but poor mechanical properties of gelatin-based hydrogels become a big obstacle that limits their wide-spread application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 42 publications
5
30
0
Order By: Relevance
“…It can be found that all the gelatin-based hydrogels formed a homogenous three-dimensional network. As reported in our previous study [ 25 ], this structure was attributed to the supporting effect of CNCs on the gelatin matrix. All hydrogels presented a cellular structure with smooth walls, and no CNCs can be clearly identified in the pore wall of the scaffold.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…It can be found that all the gelatin-based hydrogels formed a homogenous three-dimensional network. As reported in our previous study [ 25 ], this structure was attributed to the supporting effect of CNCs on the gelatin matrix. All hydrogels presented a cellular structure with smooth walls, and no CNCs can be clearly identified in the pore wall of the scaffold.…”
Section: Resultssupporting
confidence: 78%
“…The hydrogels exhibited thermo-reversible behavior and a general trend was that G′ declined with the increase in temperature. In the presence of mTG, chemical-physical gels were formed, where the physical networks (self-assembly triple helix, hydrogen bonding and hydrophobic linkages) have cooperated with covalent cross-linking [ 25 , 31 ] to maintain the stability of the hydrogel. With the increasing temperature, the collagen triple helix unfolding was activated and other physical cross-linking interactions became progressively weaker.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the antitumor drugs' different physicochemical properties, encapsulating multiple anticancer medicines in a single nanoparticle has proved difficult (Yu et al, 2014 ; Tu et al, 2017 ; Rao et al, 2018 ; Xu et al, 2018 ). Bio-degradable nanoparticles, which are created by en5FUulating a variety of medications with discrete physico-chemical behaviors and controlling their controlled releasing in regulated proportions, are thus thought to be more effective at delivering drugs to cancer cells (Lee & Nguyen, 2013 ; Li et al, 2014 ; Dong et al, 2021 ). Hybrid anticancer delivery may be used to achieve combination treatment with a sensitizer (Mao et al, 2021 ; Pragya et al, 2021 ; Tran et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%